2009
DOI: 10.1128/aem.01333-09
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Features of Resident Biofilms Determine Attachment of Listeria monocytogenes

Abstract: Planktonic Listeria monocytogenes cells in food-processing environments tend most frequently to adhere to solid surfaces. Under these conditions, they are likely to encounter resident biofilms rather than a raw solid surface. Although metabolic interactions between L. monocytogenes and resident microflora have been widely studied, little is known about the biofilm properties that influence the initial fixation of L. monocytogenes to the biofilm interface. To study these properties, we created a set of model re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
45
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 68 publications
(70 reference statements)
2
45
0
2
Order By: Relevance
“…L. monocytogenes can adhere to abiotic surfaces such as stainless steel, glass, plastic, polymers, and rubber that are present in the food processing environment (44,102,107). These bacteria also adhere to biotic surfaces such as other microorganisms and plant and animal tissues (44). Strains of L. monocytogenes show specificity in forming biofilms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…L. monocytogenes can adhere to abiotic surfaces such as stainless steel, glass, plastic, polymers, and rubber that are present in the food processing environment (44,102,107). These bacteria also adhere to biotic surfaces such as other microorganisms and plant and animal tissues (44). Strains of L. monocytogenes show specificity in forming biofilms.…”
mentioning
confidence: 99%
“…Initial adherence is critical for biofilm formation and depends on the physiochemical properties of the environmental surfaces as well as the biofilm-forming potential of the bacterial cells (18,83,102). L. monocytogenes can adhere to abiotic surfaces such as stainless steel, glass, plastic, polymers, and rubber that are present in the food processing environment (44,102,107). These bacteria also adhere to biotic surfaces such as other microorganisms and plant and animal tissues (44).…”
mentioning
confidence: 99%
“…However, one could argue that the reduced adhesion properties of the mucoid strain could in part be attributed to the viscoelastic properties of the mucoid layer, susceptible to shear stress. In a similar study, Habimana et al [49] showed that a EPS-producing mutant strain of a Lactococcus lactis strain was found to be not only highly hydrophilic, but also unable to properly adhere on glass. It was suggested that the produced EPS substances masked the real physicochemical properties of the cell, but also was susceptible to shear stress causing a delayed early colonization and slow biofilm formation.…”
Section: Hydrophobicitymentioning
confidence: 95%
“…Evidently, bacterial pathogens, such as L. monocytogenes and S. enterica, can be entrapped in multispecies sessile communities formed on such surfaces. In addition, attachment and biofilm formation by these two species have been shown to be influenced by either the natural in situ presence of other species or just their metabolic by-products (8,10,11,24,26,27,29,32,33,37,38,39,46,58,77). For instance, the presence of Staphylococcus xylosus and Pseudomonas fragi affected the numbers of L. monocytogenes biofilm cells on stainless steel (51), while compounds present in Hafnia alvei cell-free culture supernatant inhibited the early stage of S. enterica serovar Enteritidis biofilm formation on the same material (10).…”
mentioning
confidence: 99%